Proteinase-activated Receptor 2: Springboard of Tumors - Vetvicka, David; Suhaj, Petr; Olejar, Tomas; Sivak, Ladislav; Benes, Jiri; Pouckova, Pavla (Anticancer research, 2024)
Proteinase-activated receptors (PARs) were discovered more than 25 years ago and since then, their role in cancer has been under investigation. Research has primarily focused on the receptors located on the membrane of cancer cells and their impact on metabolism, intracellular signalling, and proliferation. Regarding the host response to cancer, studies have predominantly examined the relationship of thrombin receptors (PAR-1, PAR-3, and PAR-4) with blood clotting in distant metastatic spread. However, limited studies have examined the role of PARs, especially PAR-2, in the host anti-tumor immunity. This review article provides insights into the role of PAR-2 on cancer cells and immune competent cells involved in cancer development and progression. It also discussed the current knowledge of the importance of PAR-2 activation at various stages of cancer progression and its association with cancer-related pain.
Keywords: receptor PAR-2; nádory; lidé; Signal Transduction; PAR-2; proteinases; review; signální transdukce; Neoplasms; Receptor, PAR-1; fibroblasts; Humans; thrombin; Receptor, PAR-2; cancer; trypsin; receptor PAR-1